Preparation and adsorption properties of nanostructured composites derived from Al/Fe nanoparticles with respect to arsenic - Kazantsev, Sergey O. (Nanomaterials)
Composite nanostructures containing iron in different forms exhibit a high adsorption capacity with respect to arsenic. The aim of our study was to investigate the adsorption activity of an adsorbent composite prepared by the oxidation of bimetallic Al/Fe nanoparticles under different conditions. Depending on the oxidation conditions, nanostructures with different morphologies in the form of nanosheets, nanoplates and nanorods with different compositions and textural characteristics could be obtained. The nanostructures obtained had a positive zeta potential and were characterized by a high specific surface area: 330 m2/g for the AlOOH/FeAl2 nanosheets; 75 m2/g for the AlOOH/Fe2O3/FeAl2 nanoplates; and 43 m2/g for the Al(OH)3/FeAl2 nanorods. The distribution of an FeAl2 intermetallide over the surface of the AlOOH nanostructures led to an increase in arsenic adsorption of 25% for the AlOOH/FeAl2 nanosheets and of 34% for the AlOOH/Fe2O3/FeAl2 nanoplates and Al(OH)3/FeAl2 nanorods. The adsorption isotherms matched most preciously to the Freundlich model. This fact indicated the energy heterogeneity of the adsorbent surface and multilayer adsorption. The nanostructures studied can be used to purify water contaminated with arsenic.